A Quality Improvement Collaborative for Pediatric Sepsis: Lessons Learned. Issue 1 (January 2018) - Paul, Raina; Melendez, Elliot; Wathen, Beth; Larsen, Gitte; Chapman, Laura; Wheeler, Derek S.; Wakefield, Toni; Macias, Charles G.
Abstract : Background: Sepsis is a leading cause of morbidity and mortality in children worldwide. Barriers exist for timely recognition and management in emergency care settings. This 1-year quality improvement collaborative sought to reduce mortality from sepsis. Methods: Fifteen hospitals participated initially. We included children with a spectrum of illness from sepsis to septic shock. The intervention bundle focused on recognition, escalation of care, and the first hour of resuscitation. We conducted monthly learning sessions and disseminated data reports of site-specific and aggregated metrics to drive rapid cycle improvement. Results: Seven sites contributed enough data to be analyzed. Of the 1, 173 pediatric patients in the total cohort, 506 presented with severe sepsis/septic shock. Quarterly data demonstrated a mean improvement in initial clinical assessment from 46% to 60% ( P < 0.001) and in adherence to the administration of first fluid bolus within 15 minutes from 38% to 46% ( P < 0.015). There was no statistically significant improvement in other process metrics. There was no statistically significant improvement in mortality for the total cohort (sepsis to septic shock) or either of the subgroups in either 3- or 30-day mortality. Conclusions: A quality improvement collaborative focused on improving timely recognition and management of pediatric sepsis to septic shock led to some process improvements but did not show improvement in mortality. Future national efforts should standardize definitions and processes of care for sepsis to septic shock, including the identification of a "time zero" for measuring the timeliness of treatment.